Arabic Language: between Learning Necessity and Responsibility (ar) - Hamidah Hamidah (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2019)
This article aims to explain the position of Arabic language, its role and the orientation of learning it. It also tells about how muslim people respond to it, and how they take responsibility to give their children Arabic learning. In fact, not all Indonesian muslims learn Arabic whereas it is the language used in the pray and in the Holy Quran and Hadith, the two main sources of Islamic teachings. The role of Arabic also can be noticed in the development of Islamic studies and civilization. It is also as the means of communication, and international relation and diplomacy as well. Recently the orientation of the Arabic learning also changes not only for religious but also professional and economic purposes. In the religious context, every muslim is obliged to learn Arabic as much as he can to help him do the prayer. To understand the Quran and Hadith, and to master in Islamic studies, he has to learn Arabic, and so does those who teach Islamic lessons in the school, Arabic teachers and other muslim academics. Parents should pay special intention to their children